Reports and removals of child maltreatment-related hospitalizations: a population-based study - Rebbe, Rebecca (Child maltreatment, 2022)
Despite U.S. child protective services (CPS) agencies relying on mandated reporters to refer concerns of child maltreatment to them, there is little data regarding which children mandated reporters decide to report and not to report. This study addresses this gap by utilizing a population-based linked administrative dataset to identify which children who are hospitalized for maltreatment-related reasons are reported to CPS and which are removed by CPS. The dataset was comprised of all children born in Washington State between 1999 and 2013 (N = 1,271,416), all hospitalizations for children under the age of three, and all CPS records. We identified maltreatment-related hospitalizations using standardized diagnostic codes. We examined the records for children with maltreatment-related hospitalizations to identify hospitalization-related CPS reports and if the child was removed from their parents. We tested for differences in these system responses using multinomial regression. About two-thirds of children identified as experiencing a child maltreatment-related hospitalization were not reported to CPS. We found differences in responses by maltreatment subtype and the type of diagnostic code. Children whose hospitalizations were related to abuse and associated with a specific maltreatment code had increased odds of being both reported to CPS and subsequently removed by CPS.